1973
DOI: 10.1017/s0022112073000935
|View full text |Cite
|
Sign up to set email alerts
|

Stability of a circular cylinder oscillating in uniform flow or in a wake

Abstract: The lift and drag forces were measured on both a single circular cylinder and tandem circular cylinders in uniform flow at Reynolds numbers from 40 to 104, to investigate the stability of an oscillating cylinder. A cylinder (the downstream one in the tandem case) was made to oscillate in either the transverse or longitudinal direction (perpendicular or parallel to the stream). In the case of a single cylinder, its oscillation causes the so-called synchronization in a frequency range around the Strouhal frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
121
3
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(147 citation statements)
references
References 4 publications
19
121
3
1
Order By: Relevance
“…The situation where the cylinders are aligned to the flow direction ͑the so-called tandem arrangement͒ has been of particular interest and a critical spacing ͑around 3.8 cylinder diameters͒ has long been detected by Ishigai et al 3 This feature has since been confirmed in high Reynolds number flows. [4][5][6] To our knowledge, the only low Reynolds number experiments of Tanida et al 7 shows a discontinuity in the drag coefficient curve for a spacing around of 3.9 diameters. These results were further confirmed by Ohmi and Imaichi 8 and by the recent numerical simulations of Meneghini et al 9 and Sharman et al 10 To our knowledge, the most complete description of the tandem cylinder wake at low Reynolds numbers was recently given by Mizushima and Suehiro.…”
Section: Introductionmentioning
confidence: 69%
“…The situation where the cylinders are aligned to the flow direction ͑the so-called tandem arrangement͒ has been of particular interest and a critical spacing ͑around 3.8 cylinder diameters͒ has long been detected by Ishigai et al 3 This feature has since been confirmed in high Reynolds number flows. [4][5][6] To our knowledge, the only low Reynolds number experiments of Tanida et al 7 shows a discontinuity in the drag coefficient curve for a spacing around of 3.9 diameters. These results were further confirmed by Ohmi and Imaichi 8 and by the recent numerical simulations of Meneghini et al 9 and Sharman et al 10 To our knowledge, the most complete description of the tandem cylinder wake at low Reynolds numbers was recently given by Mizushima and Suehiro.…”
Section: Introductionmentioning
confidence: 69%
“…So does C D (Tanida, Okajima & Watanabe 1973). Zdravkovich (1982) concluded that the main feature of vortex shedding synchronizing with an oscillating cylinder was to magnify greatly C D and C L , compared with a stationary cylinder.…”
Section: Discussionmentioning
confidence: 99%
“…7,10,11,13 Basically, the flow patterns can be divided into two regimes by a "critical spacing" ͑S c ͒. In the case of Re= 100, the value of S c is between 3.75 and 4, according to Sharman et al 13 The different types of vortex streets are shown in the vorticity contours for Re= 100 in Fig.…”
Section: Flow Patterns For Flow Over Two Stationary Tandem Cylinmentioning
confidence: 96%
“…The literature concerning flow over two stationary tandem cylinders includes experimental observations 7,10,11 and numerical simulations. [12][13][14][15] Physical mechanisms involved in two tandem cylinders are very different from those in a single cylinder because the wakes that are shed from both cylinders are coupled and interact with each other.…”
Section: Introductionmentioning
confidence: 99%